Are more muscle-strengthening exercise participations associated with weight status in children and adolescents? Results from 67,281 participants - Huadong Su; Xinli Chi; Hui Li; Songjian Du; Jin Yan (BMC Public Health)
Abstract Purpose The aim of this study was to explore association between muscle-strengthening exercise (MSE) days and weight status in Chinese children and adolescents. Methods Cross-sectional data of 67,281 Chinese adolescents aged 10–17 years (mean age = 13.0 years, 51.9% males) was collected using online questionnaires. Validated questionnaires were used to collected data on variables (days of MES and weight status, sociodemographic characteristics) of interest in this study. The Chinese Children and Adolescents Weight Status Workforce Standard was used to categorize weight status into three groups: non-overweight/obesity, overweight, and obesity. A series of multilevel generalized linear models were used to analyse associations between days of MSE and weight status. Results were presented as odds ratio (OR) with 95% confidence interval (CI). Results In total, 34,909 boys (51.9%) and 32,372 girls (48.1%), respectively, were included in the current study. In the overall sample, those who engaged in MSE for 2 or more days had lower odds of overweight and obesity (p for trend < 0.001; OR for 2 days: 0.88, 95%CI: 0.84–0.93; OR for 3 days: 0.91, 95% CI: 0.86–0.96; OR for 4 days: 0.79, 95%CI: 0.74–0.85; OR for 5 days: 0.82, 95%CI: 0.76–0.88; OR 6 days: 0.69, 95%CI: 0.60–0.79; OR for 7 days: 0.71, 95%CI: 0.66–0.77). The associations between MSE and weight status were more pronounced in boys and younger participants. However, there was no clear pattern between MSE days and weight status among high school students. Results on subgroup analyses showed inverse associations between days of engaging in MSE per week and overweight and obesity in those not meeting the physical activity guidelines, except for girls (p = 0.179) and high school students (p = 0.449). Conclusions More days of MSE participation may be a protective factor that can prevent or control overweight and obesity in children and adolescents. However, given the study limitations in nature, future studies are recommended to confirm the association between MSE and weight status.